Too late ebook - Hoover, Colleen (2023)
The instant #1  New York Times  and  USA Today  bestseller, a story about a woman caught in a dangerous web of obsessive love, trying to find a way out before it’s too late…  this new, updated edition is  a “barn-burner” ( New York Post ) and Colleen Hoover’s darkest romantic thriller since  Verity . Sloan will go through hell and back for those she loves. And she does so, every single day. Caught up with the alluring Asa Jackson, a notorious drug trafficker, Sloan has finally found a lifeline to cling to, even if it’s meant compromising her morals. She was in dire straits trying to pay for her brother’s care until she met Asa. But as Sloan became emotionally and economically reliant on him, he in turn developed a disturbing obsession with her—one that becomes increasingly dangerous every day. When undercover DEA agent Carter enters the picture, Sloan’s surprised to feel an immediate attraction between them, despite knowing that if Asa finds out, he will kill him. And Asa has always been a step ahead of everyone in his life, including Sloan. No one has ever gotten in his way. No one except Carter. Together, Sloan and Carter must find a way out before it’s too late…